Chapter 1 Introduction - Thomson, Harriet (Taylor & Francis, 2018)
This book aims to provide a global perspective on energy poverty, with the aid of novel theoretical approaches that disturb entrenched scientific preconceptions and policy prescriptions. We are particularly interested in deepening existing conceptualizations of the systemic drivers of energy poverty, by drawing attention to the manner in which the condition is embedded in deeper forms and practices of social exclusion and injustice. Starting from the fact that energy poverty is an inherently spatial phenomenon - it is both experienced in and caused by the entanglement of the socio-technical infrastructures of the home, while varying significantly across cities, regions and nations - there is a strong focus on the geographic processes and contingencies that underpin the emergence of this predicament. We draw together the findings of original research conducted by leading experts from a wide range of countries in order to capture the rapidly expanding corpus of scientific and policy expertise on energy poverty. By furthering knowledge on the driving forces of the condition, the book also produces policy-relevant insights that can aid decisionmaking on how domestic energy deprivation can be ameliorated.